PERAN DAN FUNGSI GURU SEKOLAH DASAR DALAM MEMAJUKAN DUNIA PENDIDIKAN - Heri Maria Zulfiati (Universitas Sarjanawiyata Tamansiswa, 2014)
The role and function of teachers is very important in teaching and educating students, as well as in advancing education. The quality of student education and depend on and teacher’s quality. Teacher is a profession who prepare human resources to meet nation building in the independence. Teacher as one component of course inseparable from the education system. The paradigm of the national education system should include a variety of factors, including input, process, and output of education. In practice, more emphasis on education efforts to raise learners do something beneficial to the interests of society and the nation. So the teacher's role in creating an exciting and fun learning, teachers demanding more creative and professional. This is important, because in every lesson, has a very central role, well as planners, implementers, and evaluators in learning.